Expression of protease nexin-1 and plasminogen activators during follicular growth and the periovulatory period in cattle - Cao, M. J.; Buratini, J.; Lussier, J. G.; Carriere, P. D.; Price, C. A. (Bio Scientifica Ltd, 2006)
Extracellular matrix remodeling occurs during ovarian follicular development, mediated by plasminogen activators (PAs) and PA inhibitors including protease nexin-1 (PN-1). In the present study we measured expression/activity of the PA system in bovine follicles at different stages of development by timed collection of ovaries during the first follicular wave and during the periovulatory period, and in follicles collected from an abattoir. The abundance of mRNA encoding PN-1, tissue-type PA (tPA), urokinase (uPA) and PA inhibitor-1 (PAI-1) were initially upregulated by human chorionic gonadotropin (hCG) in bovine preovulatory follicular wall homogenates. PN-1, PAI-1 and tPA mRNA expression then decreased near the expected time of ovulation, whereas uPA mRNA levels remained high. PN-1 concentration in follicular fluid (FF) decreased and reached the lowest level at the time of ovulation, whereas plasmin activity in FF increased significantly after hCG. Follicles collected from the abattoir were classified as non-atretic, early-atretic or atretic based on FF estradiol and progesterone content: PN-1 protein levels in FF were significantly higher in non-atretic than in atretic follicles, and plasmin activity was correspondingly higher in the atretic follicles. No changes in PN-1 levels in FF were observed during the growth of pre-deviation follicles early in a follicular wave. These results indicate that PN-1 may be involved in the process of atresia in non-ovulatory dominant follicles and the prevention of precocious proteolysis in periovulatory follicles.